PENGEMBANGAN INSTRUMEN TES KALKULUS LANJUT 2 BERBASIS PEMECAHAN MASALAH - Fitrianto Eko Subekti; Reny Amalia Widiyanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
This research tried to improve the test instrument at advanced calculus 2. The objectives of this research was to test instrument the valid and good based on problem solving. This research uses 4-D development model of Thiagarajan (1974) which consists of four stages: define, design, develop, and disseminate. This research only ended up at the stage of develop. Test validity processed by test proporsion, whereas testing of result analyzable by validity, and reliability. Product of the research show (1) the test instrument developed was proved to be valid by the validator with the following averaged scores 3,05 and 3,18 from the maximal averaged score 4, (2) the analysis of experiment producted test instrument which validity and reliability. Based on the overall findings from this research we can conclude that the test instrument were proved to be valid, and good. Key words : test instrument, problem solving, 4-D